Diagram Pareto dan Diagram Fishbone: Penyebab yang mempengaruhi Keterlambatan Pengadaan Barang di Perusahaan Industri Petrochemicals Cilegon Periode 2020-2022 - Arif, Rivaldi; Gunawan, Ade Gunawan (Jurnal Riset Bisnis dan Manajemen Tirtayasa, 2023)
The procurement section plays an important role in maintaining the company's survival. Cilegon Petrochemicals Industry is a company engaged in manufacturing, where the procurement process is very important to assist in the production process. The operational operations of a company can be disrupted due to delays in the procurement process. This researcher used a qualitative descriptive method with employees involved in the procurement process as research subjects to identify and analyze the reasons behind the delay in the procurement of goods for the Cilegon Petrochemicals Industry Company. The results of the study show that the causal factors that affect the delay in procurement of goods include (1) Covid Pandemic, (2) Indented goods, (3) Weather, (4) Fabricated goods, (5) Empty stock, (6) Progress project recondition, and (7) Return of inappropriate goods. The procurement department needs to overcome the causes of these delays by creating a strategy in maintaining the availability of stock in the production process for a certain period.